FEASIBILITY ANALYSIS OF A NEW INDEPENDENT FURNITURE BUSINESS IN SYAMTALIRA BAYU DISTRICT, NORTH ACEH REGENCY - Zuhra; Marzuki; Ghazali Syamni; Ristati (Journal of Accounting Research, Utility Finance and Digital Assets, 2025)
Micro, Small and Medium Enterprises (MSMEs) have an important role in driving economic growth, including in the home furnishings industry. This study aims to analyze the feasibility of the Mandiri Baru Perabot business in Syamtalira Bayu District, North Aceh Regency, by considering market, technical, management, and financial aspects. The research method used is a quantitative approach with analysis of Payback Period (PP), Net Present Value (NPV), Net Benefit Cost Ratio (Net B/C), and Internal Rate of Return (IRR). The results of the study indicate that this business is feasible to be developed, with an NPV value of IDR 573,314,955, Net B/C of 2.54, IRR of 67.95%, and PP for 2 years 6 months 11 days. The main factors supporting the feasibility of this business include increasing market demand, operational efficiency, and maintained product quality. Thus, the Mandiri Baru Perabot business has good prospects for development in the future.